2009
DOI: 10.1002/sia.3116
|View full text |Cite
|
Sign up to set email alerts
|

Formation of alkane‐phosphonic acid self‐assembled monolayers on alumina: an in situ SPR study

Abstract: The formation process of n-alkane phosphonic acid CH 3 (CH 2 ) n−1 PO(OH) 2 (n = 10,12,14,18) self-assembled monolayers (SAMs), deposited from ethanol solutions on aluminum oxide, has been monitored in situ using surface plasmon resonance (SPR) spectroscopy. In addition, the two-solvent approach is used to obtain both film thickness and refractive index of the fully formed adsorbed layers. A densely packed adsorbed layer is formed only for the longest molecules with n = 18. The chain length and solution concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
1
25
0
2
Order By: Relevance
“…As such, the existence of a well‐packed self‐assembling monolayer was confirmed indirectly with dynamic contactangle measurements for an octadecylphosphonic acid coating on magnetron sputtered aluminum . Also, various other studies show the existence of SAMs with chain lengths higher than 12 carbon atoms …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…As such, the existence of a well‐packed self‐assembling monolayer was confirmed indirectly with dynamic contactangle measurements for an octadecylphosphonic acid coating on magnetron sputtered aluminum . Also, various other studies show the existence of SAMs with chain lengths higher than 12 carbon atoms …”
Section: Introductionmentioning
confidence: 66%
“…They can form a bond with the aluminium hydroxyls through an acid–base elimination condensation reaction. Different solvents are employed, being for example ethanol, water and tetrahydrofurane …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that an anodized aluminum surface coated with fluorinated alkyl phosphonic acids showed higher contact angles for water and organic liquids in comparison with the alkylsilanes with the same alkyl groups, although the reason was not clarified . Although there are some advantages of phosphonic acids for formation of SAMs on aluminum and several studies on phosphonic acid‐based SAMs on aluminum have been carried out, the formation of SAMs has not been fully understood. Recent in situ analysis revealed island growth of phosphonic acid molecules on aluminum oxide, suggesting that a monolayer is not always formed.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that the film is not only a simple double‐layer film. Most researches proposed the monolayer adsorption model for phosphonic acid molecules on the surface of Al and the solutions involved ethanol, water and THF . However, Hauffman et al .…”
Section: Resultsmentioning
confidence: 99%